Evaluation of The Achievement Development of The Sepak Takraw Sports Branch at The PSTI in Gresik Regency - Mohammad Muhyi; Hakim, Luqmanul; Moh. Hanafi (Universitas PGRI Palembang, 2025)
The purpose of the study is to evaluate the implementation and achievement of the achievement fostering program in the sepak takraw sports branch in the Sepak Takraw Association of All Indonesia (PSTI) Gresik Regency, in 2024. The type of research is evaluation research, using the CIPP (Context, Input, Porcess and Product) model. The data collection technique uses questionnaires, direct observations, and documentation. The data analysis technique uses quantitative descriptive. The results of the study show that the results of the evaluation of the achievement coaching of the sepak takraw sports branch in PSTI Gresik Regency. Context, in PSTI Gresik regency has been implemented and running well, input, good. The process has been carried out and is running well. Product, achievements have been good in the last five years in the form of achievements that have been achieved, supported by championship result documents. The recommendation is directed at the development of sepak takraw not only in the archipelago but also on the mainland. The final conclusion of achievement coaching in the Sepak Takraw sports branch of PSTI Gresik Regency has gone well, but it is still based on the islands, it is necessary to carry out a combination of achievement coaching on the mainland and islands.